Composite materials: A bibliometric analysis - J. Paulo Davim (AIMS Materials Science)
Composite materials are a vital subject in the field of materials science. Currently, composite materials are used in multiple sectors, including aerospace, automotive, medical, building, defense, furniture, electronics, energy, and sports. The Scopus database was used for bibliometric analysis, based on the term {composite materials}. The following returned the most search results in their respective categories: year, 2019; source, Journal of Applied Polymer Science; author, Hamada, H.; affiliation, Ministry of Education of China; country, China; document type, article; scientific area, materials science; and funding support, National Natural Science Foundation of China.